2018
DOI: 10.1073/pnas.1719866115
|View full text |Cite
|
Sign up to set email alerts
|

Less immune activation following social stress in rural vs. urban participants raised with regular or no animal contact, respectively

Abstract: SignificanceOur results show that a standardized laboratory psychosocial stressor causes a greater inflammatory response in young healthy participants with an urban upbringing in the absence of pets, relative to young healthy participants with a rural upbringing in the presence of farm animals. In view of the known links between persistent inflammatory states and psychiatric disturbances, and considering that many stress-associated physical and mental disorders are more prevalent in environments offering a nar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 54 publications
4
59
0
Order By: Relevance
“…Furthermore, while buildings can exacerbate pre-existing respiratory conditions, the role of the built environment in causing or preventing the development of respiratory conditions remains unclear. Recent research has shown that a diverse and abundant microbial community in house dust, which is often associated with rural farmhouses and homes with pets, is not deleterious to human health [205][206][207][208]. Longitudinal studies which point to the presence of pathobionts and antigens in the home during the first few years of life having a long-term protective effect against the development of adverse symptoms [201] lend support to the Old Friends hypothesis.…”
Section: The Lifelong Impact Of Microbial Roommatesmentioning
confidence: 98%
“…Furthermore, while buildings can exacerbate pre-existing respiratory conditions, the role of the built environment in causing or preventing the development of respiratory conditions remains unclear. Recent research has shown that a diverse and abundant microbial community in house dust, which is often associated with rural farmhouses and homes with pets, is not deleterious to human health [205][206][207][208]. Longitudinal studies which point to the presence of pathobionts and antigens in the home during the first few years of life having a long-term protective effect against the development of adverse symptoms [201] lend support to the Old Friends hypothesis.…”
Section: The Lifelong Impact Of Microbial Roommatesmentioning
confidence: 98%
“…The last decade has witnessed a marked increase in research supporting the mental and physical benefits of biodiversity and experience in natural environments (oft-referred to as green space) [74][75][76]. The interplay of potentially beneficial and detrimental experiences is central to biological buffering and the concept of resiliency; exposure to green space and elements of natural environments-including microbial-appear to play a role in psycho-biological resiliency over the life course [77][78][79].…”
Section: Clinical Ecology-houses Of the Housesmentioning
confidence: 99%
“…Biomarker research indicates that stress also has an effect on immune reactions. For instance, the release of salivary α-amylase indicated that experimental stress was higher in rural participants raised in the presence of animals [ 24 ]. Acute or chronic stress may therefore quantitatively regulate amylase activity, and thereby impact on the composition of digested carbohydrates and subsequently affect microbiota composition (discussed below).…”
Section: Digestion Of Carbohydrates: Amylase Action Critical For Smentioning
confidence: 99%